Spontaneous Recovery of Penetrating Cervical Spinal Cord Injury with Physiotherapeutic Treatment: Case Report and Review of the Literature - Yao Christian Hugues Dokponou; Mamoune El Mostarchid; Housni Abderrahmane; Niamien Patrice Koffi; Miloudi Gazzaz; Brahim El Mostarchid (Case Reports in Neurological Medicine)
Stab wounds to the cervical spine are less common than injuries from road accidents, sports injuries, and falls. The presence of vital, vascular, neural, respiratory, and digestive structures in the neck region mean that this kind of spinal injury is generally critical, and its management is a challenge. We report a unique case of a previously healthy 17-year-old adolescent admitted for quadriplegia secondary to a stab wound to the cervical spine at the C4C5 level. There was no surgical indication. The patient underwent physiotherapy. He showed spontaneous neurological improvement two weeks later and was able to sit on his own and to walk about three months of physical rehabilitation.